Evaluation of methotrexate encapsulated polymeric nanocarrier for breast cancer treatment - Verma R.; Singh V.; Koch B.; Kumar M. (My University, 2025)
Herein, Methotrexate-loaded chitosan nanoparticles (Meth-Cs-NPs) was formulated through single-step self-assembly by incorporating the ionic-gelation method. Chitosan was cross-linked with Methotrexate via a sodium tripolyphosphate (STPP) where 49 % Methotrexate was loaded in the nanoparticles (∼143 nm) and zeta potential of 34 ± 3 mV with an entrapment efficiency of 87 %. The efficacy of nanoparticles was assessed for chemically induced breast cancer treatment in the Sprague Dawley rats model. These Meth-Cs-NPs followed the Korsmeyer-Peppas model in-vitro release kinetics. Nanoparticles were further evaluated for in-vitro efficacy on triple-negative breast cancer (MDA-MB-231) cell lines. The MTT assay studies revealed that even slight exposure to Meth-Cs-NPs (IC50 = 15 µg/mL) caused 50 % cell death in 24 h. Further, hemocompatibility studies of Meth-Cs-NPs were performed, deciphered that Meth-Cs-NPs were biocompatible (hemolysis < 2 %). Additional cellular uptake was evaluated by confocal imaging. Moreover, an in-vivo pharmacokinetic study of nanoparticles in rats displayed increased plasma concentration of the drug and retention time, whereas a decrease in cellular clearance compared to free Methotrexate. Further, anti-tumor efficacy studies revealed that nanoparticles could reduce tumor volume from 1414 mm3→385 mm3 compared to free Methotrexate (1414 mm3→855 mm3). The current study presents encouraging prospects of Meth-Cs-NPs to be used as a viable breast cancer treatment modality. © 2023 Elsevier B.V.